Faktor-Faktor yang Mempengaruhi Kepuasan Pasien Rawat Inap Peserta BPJS Kesehatan di RSUD Bangkinang - Mahmudah, Mahmudah; Harnani, Yessi; Ismainar, Hetty (Jurnal Kesehatan Komunitas, 2024)
Patient satisfaction is a feeling that arises after comparing expectations with the reality obtained. The standard according to the Ministry of Health is Satisfaction of inpatients at Bangkinang Regional Hospital in 2021 was The BOR value has decreased in the last three years, namely 2019 by 57%, 2020 by 52% and 2021 by 43%. One of the causes is the Covid-19 pandemic that has occurred in the last two years. The purpose of this study was to look at the factors that affect the satisfaction of inpatients of BPJS Kesehatan participants at the Hospital. The study was conducted in the Bangkinang Regional Hospital, August 2022, with a total of 96 samples, respondents using a questionnaire. The data analysis used is univariate, bivariate and multivariate. Bivariate analysis found variables that affect patient satisfaction are empathy (p = 0.011), responsiveness (p=0.009), reliability (p=0.014) and patient experience (p=0.007). The variables that have no effect are assurance (p=0.238) and tangible (p=0.073). Multivariate analysis obtained two confounding variables, namely assurance and tangible. The dominant variable that has an effect is patient experience, with a POR value of 7.495. This research suggests that the hospital must equip facilities in the inpatient room, especially the call bell, provide training to improve the competence of officers, ESQ training, and provide links, social media accounts or Google Forms to respond to patient complaints quickly and effectively.